2022
DOI: 10.1155/2022/1802204
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pharmaceutical Residues and Antibiotic-Resistant Bacteria in Water and Sediments from Major Reservoirs (Owabi and Barekese Dams) in Ghana

Abstract: The presence of pharmaceuticals in the environment is undesirable since their biological activity may impair ecosystem health of reservoirs that receive inflows from other water sources. This work determined the concentrations of analgesics and antibiotics, and the occurrence of antimicrobial resistance among microbes in water and sediment samples from Owabi and Barekese reservoirs—two main sources of pipe-borne water in the Kumasi metropolis in Ghana. The study also assessed the knowledge, attitude, and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
3
6
0
Order By: Relevance
“…Apart from paracetamol (analgesic) and cipro oxacin (antibiotic) detected at concentrations of 0.029-0.1142mg/L and 0.074-0.232 mg/L respectively in e uent samples from KATH, the rest were all below detection levels (Table 4). Similar to observations made by Azanu et al (2018) and Gyesi et al, (2022), the concentrations of pharmaceuticals detected were generally low. Ibuprofen and amoxicillin were below detection level possibly because they are not administered due to respective development of tolerance and resistance for them.…”
Section: Occurrence Of Pharmaceuticals In Hospital E Uentssupporting
confidence: 84%
“…Apart from paracetamol (analgesic) and cipro oxacin (antibiotic) detected at concentrations of 0.029-0.1142mg/L and 0.074-0.232 mg/L respectively in e uent samples from KATH, the rest were all below detection levels (Table 4). Similar to observations made by Azanu et al (2018) and Gyesi et al, (2022), the concentrations of pharmaceuticals detected were generally low. Ibuprofen and amoxicillin were below detection level possibly because they are not administered due to respective development of tolerance and resistance for them.…”
Section: Occurrence Of Pharmaceuticals In Hospital E Uentssupporting
confidence: 84%
“…Pharmaceuticals have been detected in samples from dumpsites [14 ] , hospital effluents [15 ] , surface water [16] , [17] , and drinking water [18 ] all over the world. It has been noted that unwanted or expired medicines are most commonly thrown into trash cans or disposed of alongside household waste [19] , [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…This makes rivers and drinking water samples possible hotspots as well. Pharmaceuticals have been detected in food, hospital effluents, dumpsite leachates, surface and drinking water in some parts of Ghana [14] , [16] , [24] , [25] , [26] . However, the residual concentrations, occurrence, and ecological effects of antibiotics and analgesics in the Sunyani Municipality are obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, TC is an antibiotic that is mainly used to cure bacterial infections [18], mainly through its application in animal feed 19 . on the other hand, in a scienti c study, a signi cant correlation was observed between the concentration of TC in sewerage and the numeral antibiotic-resistant bacteria 20,21 . If these types of bacteria enter the human body, they can pose a serious threat by limiting the effectiveness of medical prescription because they have become resistant to the TC 22,23 .…”
Section: Introductionmentioning
confidence: 95%